A Methodology for the Assessment of the Quality of Information from Robbery Events to Enrich Situational Awareness in Emergency Management Systems - Souza, Jessica [UNESP]; Botega, Leonardo; Segundo, Jose Eduardo Santarem; Berti, Claudia (Elsevier, 2015)
Situation assessment (SA) is a significant process for the acquisition, maintenance and recovery of Situation Awareness (SAW). This process can be degraded if fed with low quality information, undermining the understanding of situations and consequently the decision-making process. Also, the major incidents related to emergency management happened due to a bad SAW, endangering people and properties. In order to assist the acquisition of the first level of SAW in the context of the assessment of robbery situations, this work aims to present a methodology to provide support to the development of emergency management systems that must be enriched by cues about information quality. Such methodology is composed by the gathering of requirements for the robbery domain, the establishment of quantitative metrics for information quality assessment, such as completeness and timeliness, the development of an ontology to capture and represent the semantic knowledge and the enforcement of the assessment functions according to score sets and the quality metrics. Finally, it is addressed a case study in the analysis of robbery reports to illustrate the applicability of the methodology. Results indicate that the proposed procedures were able to assess and semantically represent the quality of entities and attributes such as victims and criminals, that shall contribute to crucial moments in the situation assessment process.
Keywords: Data quality methodology; Information management; Knowledge management; Situational Awareness